2017
DOI: 10.1074/jbc.m116.773788
|View full text |Cite
|
Sign up to set email alerts
|

A hot spot on interferon α/β receptor subunit 1 (IFNAR1) underpins its interaction with interferon-β and dictates signaling

Abstract: Edited by Luke O'NeillThe interaction of IFN-␤ with its receptor IFNAR1 (interferon ␣/␤ receptor subunit 1) is vital for host-protective anti-viral and anti-proliferative responses, but signaling via this interaction can be detrimental if dysregulated. Whereas it is established that IFNAR1 is an essential component of the IFNAR signaling complex, the key residues underpinning the IFN-␤-IFNAR1 interaction are unknown. Guided by the crystal structure of the IFN-␤-IFNAR1 complex, we used truncation variants and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 35 publications
2
20
0
Order By: Relevance
“…This analysis unexpectedly demonstrated that IFNε bound IFNAR1-ECD with higher affinity than IFNAR2-ECD, different from data reported for the IFNα which have a higher affinity for IFNAR2 (29). As expected, the affinity of the mIFNβ-IFNAR1 interaction as measured by MST was consistent with our previous report using surface plasmon resonance (32). Notably, the affinity of the mIFNβ-IFNAR1 interaction was higher than that observed for the human IFNβ-IFNAR1interaction (29).…”
Section: Discussionsupporting
confidence: 62%
“…This analysis unexpectedly demonstrated that IFNε bound IFNAR1-ECD with higher affinity than IFNAR2-ECD, different from data reported for the IFNα which have a higher affinity for IFNAR2 (29). As expected, the affinity of the mIFNβ-IFNAR1 interaction as measured by MST was consistent with our previous report using surface plasmon resonance (32). Notably, the affinity of the mIFNβ-IFNAR1 interaction was higher than that observed for the human IFNβ-IFNAR1interaction (29).…”
Section: Discussionsupporting
confidence: 62%
“…The interface on IFNAR1‐SD4 may be specific to IFNβ or specific to the murine system, because a comparable crystal structure with human IFNβ is yet to be determined. The majority contacts with IFNAR1 SD1‐3 is consistent with biochemical analyses that show this region is sufficient for in vitro ligand binding whereas SD4 is dispensable 21,60,98,99 (Fig. 2).…”
Section: Role Of Ifnars In Human Diseasesupporting
confidence: 83%
“…2). On SD3, two prominent residues, Tyr240 AR1 (the homologous Phe238 in human IFNAR1 is also a “hot‐spot” residue in the interface with IFNα and IFNω) and the unique Tyr274 AR1 form a “hot‐spot” of interaction in the IFNAR1‐IFNβ interface; these residues are also important in determining the magnitude of the signaling response and biologic activities exhibited by IFNβ 99 . Residues that make minor contributions to the ligand interface are also found on other regions of SD1‐3 AR1 (Fig.…”
Section: Role Of Ifnars In Human Diseasementioning
confidence: 99%
See 2 more Smart Citations